No early gender effects on energetic status and life history in a salmonid. Issue 12 (December 2015) - Régnier, Thomas; Labonne, Jacques; Chat, Joëlle; Yano, Ayaka; Guiguen, Yann; Bolliet, Valérie
Abstract : Throughout an organism's early development, variations in physiology and behaviours may have long lasting consequences on individual life histories. While a large part of variation in critical life-history transitions remains unexplained, a significant proportion may be caused by early gender effects as part of gender-specific life histories shaped by sexual selection. In this study, we investigated the presence of early gender effects on the timing of emergence from gravel and the energetic status of brown trout ( Salmo trutta ) early stages. To investigate this question, individual measures of emergence timing, metabolic rate and energetic content were coupled for the first time with the use of a recent genetic marker for sdY (sexually dimorphic on the Y-chromosome), a master sex-determining gene. Our results show that gender does not influence the energetic content of emerging juveniles or their emergence timing. These findings suggest that gender differences may appear later throughout salmonid life history and that selective pressures associated with the critical period of emergence from gravel may shape early life-history traits similarly in both males and females.